A new species of the genus Gaucha Mello-Leitão, 1924 from Minas Gerais, Brazil (Solifugae, Mummuciidae) - Souza, Maysa F.v.r.; Ferreira, Rodrigo L.; Carvalho, Leonardo S. (Zootaxa, 2021)
A new sun-spider species of the ibirapemussu species-group of the genus Gaucha is described based on males and a female collected in Southeastern Brazil. The newly described species can be readily distinguished from its congeners by the reduction of the cheliceral fixed finger, distal tooth (FD), closely positioned and smaller than the medial tooth (FM); the presence of cheliceral fixed finger profondal subproximal (PFSP) and retrofondal submedial (RFSM) teeth; and by the cheliceral movable finger, medial tooth (MM) well developed, larger than submedial tooth (MSM) and smaller than proximal tooth (MP). This is the thirteenth described species in the genus Gaucha, all known from South America.